Evaluasi Implementasi Pelaksanaan Program Desa Mandiri Benih (DMB) Pada Kelompok Mutiara Tani Kelurahan Tanah Garam Kecamatan Lubuk Sikarah Kota Solok - Muharama Yora; Yusmi Nelvi; Mahmud (PUCUK : Jurnal Ilmu Tanaman, 2024)
This study, Evaluation of the Implementation of the Independent Seed Village Program (DMB) at the Mutiara Tani Farmer Group in Tanah Garam Village, Solok City, has been implemented for 2 months. This study aimed to determine the level of success of the DMB output, results, benefits, and impacts, as well as determine the problems faced by the Mutiara Tani Farmer Group in producing seeds. The method used in this study is the census method. The population in this study were all members of the Mutiara Tani farmer group who were members of the Independent Seed Village group as many as 20 people. To compare their income was taken from the Non-DMB group of as many as 20 people. The study result showed that the output, value, and score of effective seed production facilities with a score of 340 was small from a minimum score of 356. The results (outcome), increased the ability of the Serumpun farmer group to produce seeds to meet seed needs in their area. Benefits (benefits), the benefits of the Independent Seed Village were only felt by the Mutiara Tani farmer group. The impact, income, and profits of farmers in the DMB group have increased compared to non-DMB groups.